Philosophical Concept of Space and Time: Immanuel Kant dan Isaac Newton - Thomas Kristiatmo (Extension Course Filsafat ( ECF ), 2019)
Philosophical Concept of Space and Time: Immanuel Kant dan Isaac Newton